2021
DOI: 10.1177/14648849211007038
|View full text |Cite
|
Sign up to set email alerts
|

Willing but wary: Australian women experts’ attitudes to engaging with the news media

Abstract: Numerous quantitative studies from around the world have found that women are under-represented as sources in news content. This study aims to add to the existing quantitative research by describing female experts’ attitudes about being interviewed as news sources, and their experiences of interacting with journalists. It reports the findings of semi-structured interviews with 30 Australian female academic experts from a broad range of disciplines. Almost all of the women experts in the group were willing to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…There was a perception among some of the journalists that women experts were "harder to book" (p. 1075) and required more persuasion. This view, however, does not align with findings from interviews with female experts, who have generally reported a willingness to be interviewed about their area of expertise (Niemi and Pitkänen 2016;Shine 2021). Furthermore, recent related research (Greve-Poulsen et al 2021) has found that news audiences perceive female expert sources to be as credible and competent as their male counterparts.…”
Section: Women As Sources In the Newsmentioning
confidence: 90%
“…There was a perception among some of the journalists that women experts were "harder to book" (p. 1075) and required more persuasion. This view, however, does not align with findings from interviews with female experts, who have generally reported a willingness to be interviewed about their area of expertise (Niemi and Pitkänen 2016;Shine 2021). Furthermore, recent related research (Greve-Poulsen et al 2021) has found that news audiences perceive female expert sources to be as credible and competent as their male counterparts.…”
Section: Women As Sources In the Newsmentioning
confidence: 90%
“…Journalists tend to seek sources that are authoritative, reduce uncertainty, and help in analyzing and interpreting events (Albaek, 2011;Davis, 2007;Manning, 2001;Reich, 2009;Strömbäck et al, 2013;Wien, 2014). It is important to note, however, that while a journalist might speak to a range of sources while gathering information for their article, they might only quote a handful of individuals in their final news article (Conrad, 1999;Shine, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of female representations might further perpetuate the stereotype that females are neither credible nor competent sources for scientific expertise (Carli et al, 2016; Niemi and Pitkänen, 2017; Shine, 2022). This is especially problematic given the gender divides within the sciences as females are not well-represented in most scientific fields (AAUW, 2020; Hur et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algunas personas expertas han tenido una relación complicada con el periodismo, y la falta de precisión o la omisión de algunos elementos relevantes en la redacción de los artículos suelen ser algunos puntos de tensión entre personas expertas y periodistas. A pesar de ello, las últimas investigaciones señalan un incremento de la frecuencia de la presencia de personas expertas (Shine, 2021).…”
Section: Las Personas Expertasunclassified
“…Su papel clave como contextualizadoras de los hechos y como caracterizadoras del problema social que suponen los asesinatos machistas (Morgan & Politoff, 2012) es reconocida y, a la par, demandada por las y los periodistas que elaboran las informaciones. Las organizaciones que trabajan en este ámbito también han percibido la relevancia de reaccionar con rapidez ante estos sucesos (Cullen et al, 2019), y su presencia muestra una leve tendencia al alza (Shine, 2021).…”
Section: Conclusiones Y Discusiónunclassified